2011
DOI: 10.1123/jsm.25.5.474
|View full text |Cite
|
Sign up to set email alerts
|

Juggling Balls and Roles, Working Mother-Coaches in Youth Sport: Beyond the Dualistic Worker-Mother Identity

Abstract: Despite the ubiquitous presence of mothers in sport contexts, mothers’ voices are often absent in the sport literature, particularly at the youth sport level. A phenomenological approach was used to explore the experiences of working mother volunteer youth sport coaches. A role-triad model based on the work-family enrichment and role enhancement literature provided the theoretical framework. The purpose was to understand how and why working mother-coaches mange this role triad and to identify mother-worker ski… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 46 publications
3
36
0
1
Order By: Relevance
“…Meso-Level Barriers. Similar to barriers in a coaching lifestyle of women with a family and lack of encouragement from a partner or spouse (Thorngren, 1990), a common barrier is negotiating work and life LaVoi & Dutove, 2012;Leberman & LaVoi, 2011). This topic (i.e., the work-life interface for women within the industry of intercollegiate athletics) has been researched in great depth over the last decade (Dixon & Bruening, 2005;Dixon & Sagas, 2007;Dixon, Tiell, Lough, Sweeney, Osborne, and Bruening, 2008).…”
Section: Meso-level Factorsmentioning
confidence: 99%
“…Meso-Level Barriers. Similar to barriers in a coaching lifestyle of women with a family and lack of encouragement from a partner or spouse (Thorngren, 1990), a common barrier is negotiating work and life LaVoi & Dutove, 2012;Leberman & LaVoi, 2011). This topic (i.e., the work-life interface for women within the industry of intercollegiate athletics) has been researched in great depth over the last decade (Dixon & Bruening, 2005;Dixon & Sagas, 2007;Dixon, Tiell, Lough, Sweeney, Osborne, and Bruening, 2008).…”
Section: Meso-level Factorsmentioning
confidence: 99%
“…Although maternal competencies were said to complement work competencies (e.g. Leberman & Palmer, ; Leberman & LaVoi, ), some mothers hid their motherhood to secure their organisational image (Cahusac & Kanji, ). In general, mothers indicated that they would plan their work schedules based on the contingencies of their children when possible (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…It is possible that these unmarried conference commissioners felt societal pressure to pick (i.e., career or family) and made a personal sacrifice to further their career. Women in male-dominated environments, such as collegiate athletics, report feeling pressures to pick between work and family responsibilities (LaVoi & Dutove, 2012;Leberman & LaVoi, 2011), creating a situation where women could be forced to completely leave the profession or immerse themselves in the profession, thereby sacrificing romantic relationships and family. A single woman who has (potentially unknowingly) chosen to immerse herself in her work, therefore, without wife and/or mothering duties, may also face difficulties creating an engaging life outside of work beyond traditionally feminine duties, such as caring for elderly family members (Linehan & Scullion, 2008).…”
Section: Work-life Negotiationsmentioning
confidence: 99%